1988
DOI: 10.1093/jnci/80.15.1203
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Autocrine Motility Factor in Urine as a Marker of Bladder Cancer

Abstract: Cell locomotion is an essential requirement for invasion and metastasis of malignant cells. We have previously described the characterization of a 50-kilodalton autocrine motility factor (AMF), a cytokine that stimulates motility in human tumor cells. In this study, we investigated the elaboration of this factor in vivo by human bladder carcinoma and in vitro by a cultured transitional cell carcinoma (TCC) of the bladder cell line T24P. Urine samples from patients with bladder cancer were assayed for their cap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
1

Year Published

1994
1994
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(28 citation statements)
references
References 0 publications
0
27
0
1
Order By: Relevance
“…Serum PHI activities were shown to serve as a tumor marker for monitoring patients with malignant tumors [12,13], and elevation in the PHI activity was shown to be closely correlated with the development of metastases [14]. It was reported that the presence of AMF in the urine is a marker of transitional cell carcinoma of the bladder [15]. AMF stimulates cell motility via binding to its receptor (AMF-R, gp-78).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Serum PHI activities were shown to serve as a tumor marker for monitoring patients with malignant tumors [12,13], and elevation in the PHI activity was shown to be closely correlated with the development of metastases [14]. It was reported that the presence of AMF in the urine is a marker of transitional cell carcinoma of the bladder [15]. AMF stimulates cell motility via binding to its receptor (AMF-R, gp-78).…”
Section: Discussionmentioning
confidence: 99%
“…A tumor cell-derived autocrine motility factor (AMF) was identified by its ability to induce the directed and random cell locomotion of the (self-)producing cells [4,5]. AMF was detected in the urine of patients with bladder carcinomas, potentially allowing the development of prognostic and/or diagnostic markers for bladder carcinomas [6].…”
Section: Introductionmentioning
confidence: 99%
“…70 Using immunohistochemistry, increased microvascular density as a surrogate for angiogenesis has been found to be associated with tumor progression and decreased overall survival in BC patients. 71 Furthermore, increased urinary excretion of b-FGF, 70 angiogenic factors such as autocrine motility factor (AMF), 72 AMF receptor, 73 and hyaluronic acid and its degradation products 74 have been found in BC patients and have been proposed as means of detection and tumor monitoring.…”
Section: Angiogenesismentioning
confidence: 99%
“…Ay rı ca di ğer an ji yo ge nik fak tör ler olan otok rin ha re ket li lik fak tö rü (AMF), 107 AMF re sep tö rü, 108 sik lo ok si je naz-2 (COX-2), hya lü ro nik asit ve bunla rın par ça lan ma ürün le ri nin 109 üri ner sa lı nı mı, me sa ne kan ser li has ta lar da art mak ta dır. Bu ne denle sö zü edi len bu fak tör le rin tes pit edil me si, tü mö -rün ta ki bin de önem li ola ca ğı nı dü şün dür mek te dir.…”
Section: An Ji̇ Yo Ge Nez Ge Li̇ şİ Mi̇unclassified